Genetic monitoring in ex situ populations of the endangered primate Leontopithecus chrysopygus and integrative analyses with the wild founder population - Nathalia Bulhões Javarotti; Paola Andrea Ayala-Burbano; Alcides Pissinati; Mara Cristina Marques; Dominic Wormell; Gabriela Cabral Rezende; Laurence Culot; Pedro M. Galetti Jr; Patrícia Domingues de Freitas (PLoS ONE, 2025)
Captive breeding programs have been used as a relevant strategy to maintain self-sustainable and demographically stable populations with the goal of safeguarding threatened species from their imminent risk of EXTINCTION. Thus, monitoring genetic diversity becomes essential to avoid the loss of genetic diversity and inbreeding depression throughout ex situ generations. Furthermore, such programs must carry out adequate metapopulation management to retain genetic diversity from the wild, minimizing eventual harmful effects associated with adaptation in captivity and sub-structuring. In this study, we analyzed ex situ populations of the endangered black lion tamarin (BLT), Leontopithecus chrysopygus, a primate endemic to the Brazilian Atlantic Forest. We monitored genetic diversity and structure in the three main ex situ groups for conservation purposes, before (2014) and after (2020) the transfer of five captive animals from Brazilian to European institutions. We also analyzed data from the whole studbook of the species to access life-history information about the ex situ populations. In addition, we performed an integrative ex situ/in situ analysis by including extant wild individuals from the same area of the founder population. Finally, we evaluated population viability based on genetic diversity trends predicted for the next 100 years. Our findings showed that the captive breeding program of BLT has been efficient in preventing the loss of heterozygosity despite significant reductions in allelic richness. This reduction is likely due to the loss of private and/or rare alleles resulting from the death of some individuals. The extant ex situ metapopulation and the wild population evidenced significant genetic differentiation and overall low levels of genetic diversity. The predictive analysis indicated that the loss of genetic diversity will be critical for the captive groups. However, the wild population demonstrated a greater capacity to retain genetic diversity over the next 100 years. These findings provide relevant information on the BLT’s captive breeding program and its founder-related wild population, as well as insights for further integrated ex situ/in situ management actions.